New Approaches for Preeclampsia: Review of the Literature - Emel Ebru Özçimen (Gynecology Obstetrics & Reproductive Medicine, 2015)
Preeclampsia is an important cause of maternal death and complicate 5-10% of pregnancies. The cause involves inadequate cytotrophoblastic invasion of the myometrium and maternal endothelial dysfunction. Preeclamptic women should be monitored and definitive therapy is delivery of the fetus. Hypertension in pregnancy carries risk for future in cardiovascular diseases.